Real-time multisite invasive neural recording during downhill skiing in Parkinson’s disease: a case report - Rodrigo Fernández-Gajardo; Rodrigo Fernández-Gajardo; Ro’ee Gilron; Amelia Hahn; Philip A. Starr (Frontiers in Neuroscience)
IntroductionInvasive recording of neural activity provides valuable insights into Parkinson’s disease (PD). Bidirectional sensing devices enable wireless neural data collection during everyday activities, but neural signals during complex outdoor sports remain unexplored.MethodsWe recorded neural data from a 57-year-old PD patient using bilateral implanted pulse generators connected to subthalamic nucleus (STN) and motor cortex leads. Recordings were performed in two settings: in-clinic during a computer-controlled task and outdoors during downhill skiing. Neural data were analyzed for power spectral density (PSD) and coherence across different frequencies.ResultsIn-clinic recordings demonstrated movement-related cortical and STN beta desynchronization with cortical gamma increase. Skiing similarly induced STN beta desynchronization but also elicited low-gamma activity (30–60 Hz) and unique finely-tuned gamma (FTG) activity at 85 Hz in the off-medication state, predominantly in the less affected hemisphere. Tremor-related cortical beta suppression was observed during stopping, with prominent 10 Hz activity associated with resting tremor.ConclusionReal-time multisite neural recordings during a complex outdoor activity revealed distinct neural signatures compared to in-clinic tasks. The findings suggest that self-cued, learned motor tasks elicit unique frequency bands and highlight differences based on disease asymmetry and medication state.